Availability of licensed cannabis businesses in relation to area deprivation in Washington state: A spatiotemporal analysis of cannabis business presence between 2014 and 2017. (24th October 2019) - Amiri, Solmaz; Monsivais, Pablo; McDonell, Michael G.; Amram, Ofer
Abstract: Introduction and Aims: In states where recreational use of cannabis has been legalised, increasing numbers of cannabis licensed cannabis businesses resulted in concerns about their potential social and health impacts. This study examined spatiotemporal variations in availability of cannabis licensed cannabis businesses (i.e. producers, processors and retailers) in relation to area deprivation in Washington state from 2014 to 2017. Design and Methods: Data on licensed cannabis businesses were obtained from the Washington State Liquor and Cannabis Board. The number of licensed cannabis businesses was estimated for Washington's 1446 census tracts. Census tracts were stratified into tertiles based on the Singh's Area Deprivation Index showing socio‐economic characteristics of communities (least‐deprived, middle‐deprived and most‐deprived). The Integrated Nested Laplace Approximation approach allowed for the spatial and temporal characterisation of cannabis businesses, accounting for similarities based on neighbouring census tracts. Results: The density of all licensed cannabis outlets increased over time. Most‐deprived areas have increased likelihood of licensed cannabis outlet density when compared to least‐deprived areas. No differences were observed in the likelihood of licensed cannabis outlet density in middle‐deprived areas when compared to least‐deprived areas. Discussion and Conclusions: The results of this study showed disparity with respect to licensed cannabis outlet density in Washington state over time. The findings call for initiatives, policies and research that decrease disparities in cannabis outlet locations.